Proximal femoral canal shape is more accurately assessed on AP hip radiographs than AP pelvis radiographs in primary Hip osteoarthritis - Merle, Christian; Waldstein, Wenzel; Gregory, Jennifer S.; Goodyear, Simon R.; Aspden, Richard M.; Aldinger, Peter R.; Murray, David W.; Gill, Harinderjit S. (HIP international, 2013)
The objectives of the present study were to determine (1) whether differences in the radiographic appearance of the of the proximal femoral canal exist on corresponding AP pelvis and AP hip radiographs, and (2) whether radiographic assessment of canal shape is accurate with reference to computed tomography (CT)., In a retrospective study, corresponding radiographs and CT scans of 100 consecutive patients with primary hip OA were evaluated. Active shape modelling (ASM) was performed to assess the variation in proximal femoral canal shape and to identify differences between AP hip and AP pelvis views. Differences in the medial cortical flare between radiographs and CT were quantified using least squares curve fitting., ASM identified significant differences in the assessment of canal shape on corresponding AP hip and AP pelvis views. Curve fitting demonstrated a good agreement between AP hip radiographs and CT. Agreement between AP pelvis radiographs and CT was less good., In contrast to AP pelvis radiographs, AP hip radiographs allow a more accurate and reliable assessment of proximal femoral canal shape in the frontal plane in primary hip OA. Our findings may improve stem fit in total hip arthroplasty without the routine use of CT.